Ethical Decision-making: How Twenty Years of Philosophy Changed my Life - van der Merwe, J. C. (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2006)
This article focuses on the process of ethical decision-making. I will begin with some reflections on my personal and academic life thus far to illustrate how I became interested in ethical decision-making and to discuss the influence that thinkers, such as Danie Strauss, had on my thinking. In the second part of the article I will explain my own approach to ethics, which will be followed by some remarks regarding specific philosophical tools that can be applied to ethical and moral issues.